Optimizing initial biomass to enhance microplastic sequestration via density-driven bio-flocculation in microalgal systems - Xiaoxue Mei; Jiawei Wang; Xueying Zhao; Yilu Liang; Baiyun Lu; Yawen Fan; Defeng Xing; Nanqi Ren; Yan Liu (Bioresource Technology, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.

Electrically enhanced microalgae-bacteria systems for wastewater treatment under low-temperature conditions - Qitong Cai; Zhengpeng Wang; Xinyu Li; Yan Liu; Nanqi Ren; Defeng Xing; Xiaoxue Mei; Yawen Fan (Bioresource Technology, 2026)

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Identification of a NEK7-related pyroptosis gene signature against pancreatic cancer and evaluation of its potential in tumor microenvironment remodeling via regulating inflammasome complex - Jia Liu; Zilong Yan; Tongning Zhong; Jianhua Qu; Defeng Lei; Jinglin Lai; Citing Zhang; Zhengquan Lai; Weipeng Ai; Xueqing Liu (Functional & Integrative Genomics, 2025)

Physiological stress and tissue damage response of Ctenopharyngodon idella to artificial and automated injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Chenqing Zhang; Songming Zhu; Zhangying Ye (Aquaculture International, 2025)

Sesquiterpenoids from Ferula samarkandica - Miaomiao Zhang; Mayire Nueraihemaiti; Khamidulla Kamoldinov; Defeng Yan; Yuqing Song; Nannan Xu; Guoan Zou; Haji Akber Aisa (Phytochemistry, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Enhanced photocatalytic defluorination of perfluorooctanoic acid through integrated hydrogen atoms/electrons reduction and ROS oxidation with metal–organic framework heterogeneous catalysts - Cai Yan; Zheng Zhong; Jing Wang; Kun Feng; Defeng Xing (Chemical Engineering Journal, 2025)

Landslide susceptibility assessment using AutoML-SHAP method in the southern foothills of Changbai Mountain, China - Defeng Zheng; Yuanyuan Li; Chenglin Yan; Hao Wu; Yosuke Alexandre Yamashiki; Botong Gao; Tingkai Nian (Landslides, 2025)

A review of submarine landslides associated with rapid sedimentation - Zehao Wang; Defeng Zheng; Xingsen Guo; Zhongde Gu; Chenglin Yan; Tingkai Nian (Marine Georesources & Geotechnology, 2025)

Numerical investigation of the instability process in underwater sedimentary slopes subjected to seismic action - Tingkai Nian; Zehao Wang; Defeng Zheng; Zhongde Gu; Chenglin Yan; Xingsen Guo (Engineering Geology, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

Large-scale geohazards risk of submarine landslides considering the subsea cables vulnerability: A case study from the northern continental slopes of South China Sea - Defeng Zheng; Qingkang Fang; Deyu Lei; Zehao Wang; Chenglin Yan; Ze Rong (Engineering Geology, 2024)

Improved electrocatalytic activity and CO2 tolerance of iron-based perovskite as an intermediate temperature SOFC cathode - Yunlong Chen; Jiahui Zhu; Tifeng Xia; Yuqing Feng; Jiayi Chang; Xiaofei Zhu; Jinghe Bai; Jianqiu Wang; Wenfu Yan; Defeng Zhou (Fuel, 2024)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Development of real‐time recombinase polymerase amplification ( RPA ) and RPA combined with lateral flow dipstick ( LFD ) assays for the rapid and sensitive detection of cyprinid herpesvirus 3 - Yingying Li; Ruifan Li; Xubing Mo; Yingying Wang; Jiyuan Yin; Sven M. Bergmann; Yan Ren; Houjun Pan; Cunbin Shi; Defeng Zhang; Qing Wang (Journal of Fish Diseases, 2024)
In this issue, we established rapid, cost‐effective, and simple detection methods including recombines polymerase amplification with lateral flow dipstick (RPA‐LFD) and real‐time RPA for cyprinid herpesvirus 3(CyHV‐3), and evaluated their sensitivity, specificity, and applicability, the real‐time RPA method could achieve sensitive diagnosis of CyHV‐3 within 1.3 copies per reaction, respectively. The real‐time RPA method is 10‐fold more sensitive than RPA‐LFD method. The exact number of CyHV‐3 can be calculated in each sample by real‐time RPA. The sera from koi also can be tested in these methods. In addition, no cross‐reaction was observed with other related pathogens, including carp oedema virus (CEV), spring viraemia of carp virus (SVCV), cyprinid herpesvirus 1(CyHV‐1), cyprinid herpesvirus 2(CyHV‐2), type I grass carp reovirus (GCRV‐I), type II GCRV (GCRV‐II), type III GCRV (GCRV‐III), and Aeromonas hydrophila.

Ni-doped Fe-based perovskite to obtain multifunctional and highly efficient electrocatalytic active IT-SOFC electrode - Jinghe Bai; Leilei Niu; Qiurong Zhu; Defeng Zhou; Xiaofei Zhu; Ning Wang; Wenfu Yan; Jianqiu Wang; Qingwen Liang; Cheng Wang (Fuel, 2024)

Mechanisms of metabolic regulation and enhanced methane production by hydrolytic nanozyme in sludge anaerobic digestion - Jing Wang; Cai Yan; Zheng Zhong; Baiyun Lu; Chuan Chen; Lei Zhao; Jun Ma; Defeng Xing (Chemical Engineering Journal, 2024)

Linking metabolomics to machine learning reveals the metabolic fates of the refractory industrial pollutant 1-Hexadecene - Lei Yang; Xijun Xu; Jin Yan; Wei Wang; Xueting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2024)

Termite mounds affect soil aggregate stability and aggregate-associated phosphorus forms in a tropical rubber plantation - Fangmei Lin; Yanqiang Jin; Chenggang Liu; Yan Ren; Chuan Jiang; Defeng Feng; Jianwei Tang (Plant and Soil, 2024)

A high-performance composite cathode based on thermal expansion complementation for SOFC - Ling Hu; Defeng Zhou; Xiaofei Zhu; Ning Wang; Jinghe Bai; Huifang Gong; Youjie Zhang; Yunlong Chen; Wenfu Yan; Qiurong Zhu (Fuel, 2024)

The Bacillus velezensis CYS06 Strain Exhibits Promising Applications in Fighting Grass Carp Bacterial Diseases - Lijuan Liu; Dongdong Jiang; Yan Ren; Cunbin Shi; Yajun Wang; Jiyuan Yin; Qing Wang; Defeng Zhang (Fishes, 2023)
Aeromonas septicemia and columnaris disease are major bacterial diseases in grass carp; however, the drugs currently used to control these diseases pose environmental and health risks. This study aimed to screen for a probiotic Bacillus strain with antagonistic activity to prevent and control bacterial diseases in grass carp and to evaluate the antimicrobial activities, biosafety, and biocontrol effects of this strain. A Bacillus strain with antagonistic activity against Aeromonas hydrophila, obtained from grass carp intestines, was screened, and the isolate CYS06 was identified by analyzing the 16S rRNA and gyrA gene sequences. The antimicrobial spectrum of the strain CYS06 was determined, and the activities of amylase, cellulase, protease, and lipase of the strain CYS06 were determined. The whole genome of the strain CYS06 was sequenced using the nanopore sequencing technology platform, followed by the analysis of the antagonistic substance synthesis gene clusters and CAZy enzyme gene families. The biosafety of the strain CYS06 was evaluated via intraperitoneal injection into healthy grass carp. After the strain CYS06 was fed to the grass carp, its biological control effect on this fish was evaluated through artificial infection experiments. The strain CYS06 was identified as Bacillus velezensis, based on molecular identification, which shows broad antimicrobial activity against various fish pathogens. The strain CYS06 secretes amylase, cellulase, protease, and lipase. The genome size of the strain CYS06 is 3,914,159 bp, and it contains eight antagonistic substance synthesis gene clusters and many CAZy enzymes. The strain CYS06 exhibits high biological safety for grass carp, based on the challenge test. Feeding grass carp with the strain CYS06 for 4 weeks significantly enhanced the resistance of the fish to A. hydrophila. Strain CYS06 could inhibit the growth of Flavobacterium columnare under co-culture and reduce the amount of F. columnare adherence on the gills of grass carp, indicating that CYS06 has good potential for the prevention and control of columnaris disease. In conclusion, we isolated an antagonistic probiotic strain, CYS06, which exhibits a biological control effect on septicemia and columnaris disease caused by Aeromonas spp. and F. columnare in grass carp, respectively. This strain contains many antagonistic substance synthesis-related gene clusters and holds the potential to degrade various types of carbohydrates. As a biological control agent, the strain CYS06 exhibits significant potential for the prevention and control of bacterial diseases in grass carp.

Understory vegetation management regulates soil carbon and nitrogen storage in rubber plantations - Yan Ren; Fangmei Lin; Chuan Jiang; Jianwei Tang; Zhaofei Fan; Defeng Feng; Xiaoling Zeng; Yanqiang Jin; Chenggang Liu; Olusanya Abiodun Olatunji (Nutrient Cycling in Agroecosystems, 2023)

Do ectoparasites on fish gills “talk” with gut microbiota far away? - Lin Wang; Defeng Zhang; Jun Xie; Ouqin Chang; Qing Wang; Cunbin Shi; Fei Zhao; Hua Gong; Yan Ren; Najiah Musa; Kok Leong Lee; Houjun Pan (Aquaculture, 2023)

Study on the effect of axial and hydraulic pressure coupling on the creep behaviors of sandstone under multi-loading - Defeng Liu; Wenxin Yan; Su Yan; Qinrong Kang (Bulletin of Engineering Geology and the Environment, 2021)

Spatial-temporal dynamics of soil chloride distribution in a coastal saline plain: implication for ocean and climate influences - Shaofeng Yan; Lu Zhai; Qiuliang Deng; Defeng Pan; Shikai Gao; Chaowang Zou (Journal of Soils and Sediments, 2018)